Effectiveness of tobacco cessation pharmacotherapy in the Veterans Health Administration. Issue 5 (4th September 2018) - Duffy, Sonia A; Ignacio, Rosalinda V; Kim, Hyungjin Myra; Geraci, Mark C; Essenmacher, Carol A; Hall, Stephanie V; Chow, Adam; Pfeiffer, Paul N; Sherman, Scott E; Bohnert, Kipling M; Zivin, Kara; Barnett, Paul George
Abstract : Introduction: In 2003, the Veterans Health Administration (VHA) implemented a directive that cessation pharmacotherapy be made available to all who use tobacco and are interested in quitting. Despite the efficacy of cessation pharmacotherapy shown in clinical trials, the generalisability of the results in real-world settings has been challenged. Hence, the specific aim of this study was to determine the effectiveness of cessation pharmacotherapies in the VHA. Methods: This retrospective cohort study used VHA's electronic medical record data to compare quit rates among those who use tobacco and who did vs. did not receive any type of cessation pharmacotherapy. Included were 589 862 Veterans identified as current tobacco users during fiscal year 2011 who had not received cessation pharmacotherapy in the prior 12 months. Following a 6-month period to assess treatment, quit rates among those who were treated versus untreated were compared during the 7–18 months (12 months) post-treatment follow-up period. The estimated treatment effect was calculated from a logistic regression model adjusting for inverse probability of treatment weights (IPTWs) and covariates. Marginal probabilities of quitting were also obtained among those treated versus untreated. Results: Adjusting for IPTWs and covariates, the odds of quitting were 24% higher among those treated versus untreated (OR=1.24, 95% CI 1.23 to 1.25, p<0.001). The marginal probabilities of quitting were 16.7% for the untreated versus 19.8% for the treated based on the weighted model. Conclusion: The increased quit rates among Veterans treated support the effectiveness and continuation of the VHA tobacco cessation pharmacotherapy policy.